VD_FINDINFO 42/2011/FAB vom 16. März 2011 - VD Tribunal cantonal (2011)
SOCIÉTÉ SIMPLE, CONSORITÉ, SÉQUESTRELP, DOMMAGE, INTÉRÊTFRUIT CIVIL | 530 al. 1 CO, 530 CO, 544 al. 3 CO, 548 CO, 550 CO, 273 LP